Infant CT-Dilated Ventricles and Learning Disorders - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The risk of developing learning disability at school age in extremely low birth weight (ELBW) infants showing dilated lateral ventricles on CT at postconceptual age of 40 weeks was evaluated at Akita School of Medicine, Japan.